How Aboriginal Peer Interactions in Upper Primary School Sport Support Aboriginal Identity - Kickett-Tucker, Cheryl S. (The Australian Journal of Indigenous Education, 2008)
Abstract This ethnographic study tested the hypothesis that positive social interactions in sport will contribute positively to the Aboriginal identity of urban, Australian Aboriginal children. Nine male and female children aged 11-12 years were observed and interviewed. Significant responses were extracted and meanings were identified and grouped into various themes (Colaizzi, 1978). Interactions between Aboriginal participants were different from interactions with non-Aboriginal children and each provided different sources of information toward children's Aboriginal identity. The hypothesis was supported because the outcomes of interactions in sport among Aboriginal children enabled them to positively express their Aboriginal identity together in a group, speak an Aboriginal language and interact with each other in ways that further affirmed their Aboriginal identity. In comparison, non-Aboriginal peers contributed positively to Aboriginal student's self-esteem because of the positive feedback they provided in school sport. Furthermore, non-Aboriginal students' social interactions with Aboriginal peers were purposeful for making friends, acceptance and respect between each other.